Evaluation of outcomes in conservative versus surgical management of zygomatic complex fracture in Bhairawaha, Nepal - Mishra, Ravish; Yadav, Deepak; Kandel, Laxmi; Tripathi, Shashank; Singh, Harender; Pandit, Santosh (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Zygomaticomaxillary complex (ZMC) fractures are among the most common facial fractures and can be managed either conservatively or surgically depending on severity and clinical presentation. However, the optimal approach remains debated, particularly in terms of functional and aesthetic outcomes. Hence, this study aimed to compare the clinical outcomes and complications associated with conservative versus surgical management of ZMC fractures and to identify predictors of favorable recovery. Methods: A comparative study was conducted on 60 patients diagnosed with isolated ZMC fractures, divided equally into conservative (n=30) and surgical (n=30) management groups. Demographic characteristics, fracture patterns, treatment outcomes, and complications were recorded. Clinical outcomes were categorized as excellent, good, fair, or poor. Multivariable logistic regression analysis was performed to identify factors associated with favorable recovery. Results: Patients in the surgical group were older on average than those managed conservatively. Excellent outcomes were more frequent in the surgical group (50.0%) compared to the conservative group (33.3%), while poor outcomes were less common (3.3% vs. 10.0%). Enophthalmos and cosmetic deformity were notably higher in the conservative group, affecting 26.7% and 36.7% of patients, respectively, compared to 6.7% and 13.3% in the surgical group. The incidence of nerve paresthesia, trismus, and diplopia was similar across both groups. Although surgical patients demonstrated better outcomes, surgical management was not an independent predictor of favorable recovery in multivariable analysis (p = 0.21). Cosmetic deformity was the only significant predictor of poorer recovery (p = 0.04). Conclusions: Surgical management of ZMC fractures appears to provide better clinical and aesthetic outcomes with fewer complications compared to conservative treatment. Cosmetic deformity negatively impacts recovery, highlighting the importance of appropriate treatment selection for optimal patient outcomes.